Farmers’ perceptions of fall armyworm pest management practices in Bali, Indonesia - RATNA KOMALA DEWI; I NYOMAN GEDE USTRIYANA; ZULAZMI ZULAZMI; I KADEK WISMA YUDHA (Asian Journal of Agriculture, 2026)
Abstract. Dewi RK, Ustriyana ING, Zulazmi, Yudha IKW. 2026. Farmers’ perceptions of fall armyworm pest management practices in Bali, Indonesia. Asian J Agric 10 (1): g100171. https://doi.org/10.13057/asianjagric/g100171. Maize crops in Bali, Indonesia, are widely affected by the fall armyworm (FAW) (Spodoptera frugiperda), causing significant economic losses. This study aimed to assess farmers’ perceptions of fall armyworm infestation and its perceived economic impacts, and to document pest management practices among maize farmers in Bali. This study used survey data obtained from 200 farmers from April 2024 to May 2025 across 9 districts and 1 city in Bali and was analyzed using descriptive statistics. Farmers’ education levels ranged from elementary school to bachelor’s degree, with most farmers having more than 10 years of farming experience. Approximately 52% of farmers reported 50-75% crop losses due to fall armyworm infestation during the dry season, which is perceived to affect farmers’ income. Most farmers perceived fall armyworm as a major threat to maize production. A total of 78% of farmers were able to correctly identify FAW, and 77% agreed that infestation reduces income. Emamectin benzoate was the most commonly used pesticide (28%) in pest management practices. The widespread use of synthetic pesticides was reported, often without adequate personal protective equipment, and pesticide application was not always aligned with recommended guidelines. These findings suggest the need for practical interventions, including farmer training and extension programs that can be implemented by the local government to improve pest management practices and reduce the impact of fall armyworm in Bali.